BIMBINGAN PEMULASARAAN JENAZAH MELALUI METODE DE MONSTRASI PADA KARANG TARUNA DI DESA MEDALKRISNA - Pratama, Yosse Amanda; Gunawan, Akmal Rizki; Irham, Irham; Ghofur, Abdul (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
As social creatures, humans rely heavily on each other both during life and after death. In Islamic societies, the community has the responsibility to organize funerals. However, many people don't know how to do it, so they have little intention of doing it. The method used in this corpse burial activity is through lectures, question-and-answer demonstrations and evaluation. The results of the service showed that there was an increase in the knowledge and understanding of youth organizations regarding the procedures for handling corpses, and the youth also became enthusiastic about the presentation given by the researcher, giving rise to new cadres in the Medalkrisna village environment. Through the active participation of the village community, especially the teenage youth of Karang Taruna, it is hoped that the results can be contributed by the amil in Medalkrisna village in order to improve the development of the village's own human resources. The aim of this research is of course to guide young teenagers to increase their knowledge about corpse burial so that later they can even understand corpse burial in Islam itself. It can be concluded that the implementation of this activity, especially in community service, can certainly increase knowledge and increase understanding, especially the procedures for intermenting corpses, as well as religiously training the youth of local youth organizations so that they can understand more about intermenting corpses.